Pengaruh Kualitas Kredit dan Penerapan Prinsip 5 C Terhadap Keputusan Realisasi Kredit pada Lembaga Perkreditan Desa (Lpd) Se-Kecamatan Abiansemal Kabupaten Badung - Ni Nyoman Ayu Tirtawati; Putu Ngurah Suyatna Yasa; Ita Silvia Azita Azis (Warmadewa Economic Development Journal (WEDJ), 2019)
This research is entitled "The Effect of Credit Quality and Application of 5C Principles on Credit Realization Decisions in Lembaga Perkreditan Desa (LPD) in Abiansemal District, Badung Regency". The formulation of the problem is: Does the quality of credit and the application of the 5C principle have a positive and significant effect on the decision on credit realization in Lembaga Perkreditan Desa (LPD) in the Abiansemal sub-district. The purpose of this study is: to find out whether there is a positive and significant influence between credit quality and the application of the 5C principle. The number of respondents in this study were 50 people. The data analysis used in this study is partial least square (PLS). The results of the study indicate that credit quality, the application of the 5C principle (character, capital, capacity, collateral, condition of economy) has a positive and significant influence on credit realization decisions